ANALISIS PENGARUH REWARD DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Jumawan; Alvito Dwi Wangsa; Reifa Galih Ramadhanti; Alfath Nare Utama; Herlin Rahmasari; Naufal Khairiansyah (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
The best use of labor is what human resource management entails, with an emphasis on leveraging a person's physical and mental capabilities to meet organizational or business objectives. Performance is one aspect of human resources. It is indisputable that a firm or organization will struggle to accomplish its objectives if employees don't perform well. Workplace discipline and rewards are just two of the numerous elements that promote better performance from employees. The purpose of this study is to investigate the relationship between employee performance and rewards and work discipline. This study employs qualitative methodologies, and the information gathered is based on data from earlier studies used as a guide. The findings of this study demonstrate that work discipline and rewards have a favorable and significant impact on employee performance. Consequently, a business or organization can motivate staff members to perform better by offering rewards that are appropriate.